Immunoglobulin detection in wild birds: effectiveness of three secondary anti‐avian IgY antibodies in direct ELISAs in 41 avian species. Issue 10 (28th May 2016) - Fassbinder‐Orth, Carol A.; Wilcoxen, Travis E.; Tran, Tiffany; Boughton, Raoul K.; Fair, Jeanne M.; Hofmeister, Erik K.; Grindstaff, Jennifer L.; Owen, Jen C.
Summary: 1.Immunological reagents for wild, non‐model species are limited or often non‐existent for many species. 2. In this study, we compare the reactivity of a new anti‐passerine IgY secondary antibody with existing secondary antibodies developed for use with birds. Samples from 41 species from the following six avian orders were analysed: Anseriformes (1 family, 1 species), Columbiformes (1 family, 2 species), Galliformes (1 family, 1 species), Passeriformes (16 families, 34 species), Piciformes (1 family, 2 species) and Suliformes (1 family, 1 species). Direct ELISAs were performed to detect total IgY using goat anti‐passerine IgY, goat anti‐chicken IgY or goat anti‐bird IgY secondary antibodies. 3.The anti‐passerine antibody exhibited significantly higher IgY reactivity compared to the anti‐chicken and/or anti‐bird antibodies in 80% of the passerine families tested. Birds in the order Piciformes (woodpeckers) and order Suliformes (cormorants) were poorly detected by all three secondary antibodies. A comparison of serum and plasma IgY levels was made within the same individuals for two passerine species (house finch and white‐crowned sparrow), and serum exhibited significantly more IgY than the plasma for all three secondary antibodies. This result indicates that serum may be preferred to plasma when measuring total antibody levels in blood. 4.This study indicates that the anti‐passerine IgY secondary antibody can effectively be used in immunological assays to detect passerine IgY for species in most passerine families and is preferred over anti‐chicken and anti‐bird secondary antibodies for the majority of passerine species. This anti‐passerine antibody will allow for more accurate detection and quantification of IgY in more wild bird species than was possible with previously available secondary antibodies.